2015
DOI: 10.1136/bjsports-2015-094913
|View full text |Cite
|
Sign up to set email alerts
|

How reliable are Functional Movement Screening scores? A systematic review of rater reliability

Abstract: This review found 'moderate' evidence that raters can achieve acceptable levels of inter-rater and intra-rater reliability of composite FMS scores when using live ratings. Overall, there were few high-quality studies, and the quality of several studies was impacted by poor study reporting particularly in relation to rater blinding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 53 publications
2
35
0
3
Order By: Relevance
“…Consistent with a previous systematic review of rater reliability for FMS composite scores that noted poor quality of study reporting,15 we also observed deficits in reporting quality, with essential study characteristics such as participant age and loss to follow-up not reported in some studies. Several studies also lacked precision in reporting the duration of injury surveillance, which was often limited to descriptions such as ‘one season’.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with a previous systematic review of rater reliability for FMS composite scores that noted poor quality of study reporting,15 we also observed deficits in reporting quality, with essential study characteristics such as participant age and loss to follow-up not reported in some studies. Several studies also lacked precision in reporting the duration of injury surveillance, which was often limited to descriptions such as ‘one season’.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the j values that we observed were similar to those reported for interrater reliability between expert and novice raters (j range ¼ 0.46-0.88). 26 In a recent literature review, Moran et al 27 examined the reliability of another common movement assessment, the Functional Movement Screen (FMS), and reported moderate evidence of acceptable live interrater scoring of the FMS (j 0.4). Novice raters had moderate to high reliability (j range ¼ 0.54-1.00; j avg ¼ 0.74 6 0.15), with associated percentage agreement ranging from 74.4% to 100.0%, whereas expert FMS raters had slightly lower reliability (j range ¼ 0.40-0.95; j avg ¼ 0.68 6 0.17), with associated percentage agreement ranging from 69.2% to 97.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The FMS is a seven task test (5, 6) comprising the following whole-body movements: 1) acceptable (20).…”
Section: Functional Movement Screen™ (Fms)mentioning
confidence: 99%